3 - Failed or Self-Hindering Prophecies? Employment Experiences of African Graduates in the 1990s: Alexis-Michel Mugabushaka, Ulrich Teichler & Harald Schomburg - Alexis-Michel Mugabushaka,; Ulrich Teichler,; Harald Schomburg, (Journal of Higher Education in Africa, 2003)
The 1980s brought about sweeping and far-reaching structural changes in many African countries, which greatly affected the higher education sector. Though, the task of training the professional and political elite had been achieved in the previ- ous decades, early reforms now faced new challenges. Concerns were raised that, without substantial new reforms, there may be a mismatch between higher educa- tion and the labor market, leading to massive unemployment among graduates, a tedious transition process from higher education to the labour market, and the un- deremployment of highly skilled laborers in low-skill jobs. This article uses survey data, conducted in Ghana, Kenya, Malawi, Nigeria, Tanzania, and Uganda to exam- ine the basis of such concerns. The 1980s brought about sweeping and far-reaching structural changes in many African countries, which greatly affected the higher education sector. Though, the task of training the professional and political elite had been achieved in the previ- ous decades, early reforms now faced new challenges. Concerns were raised that, without substantial new reforms, there may be a mismatch between higher educa- tion and the labor market, leading to massive unemployment among graduates, a tedious transition process from higher education to the labour market, and the un- deremployment of highly skilled laborers in low-skill jobs. This article uses survey data, conducted in Ghana, Kenya, Malawi, Nigeria, Tanzania, and Uganda to exam- ine the basis of such concerns.